Endosteal-like extracellular matrix expression on melt electrospun written scaffolds. (1st April 2017) - Muerza-Cascante, Maria Lourdes; Shokoohmand, Ali; Khosrotehrani, Kiarash; Haylock, David; Dalton, Paul D.; Hutmacher, Dietmar W.; Loessner, Daniela
Graphical abstract: Abstract: Tissue engineering technology platforms constitute a unique opportunity to integrate cells and extracellular matrix (ECM) proteins into scaffolds and matrices that mimic the natural microenvironment in vitro . The development of tissue-engineered 3D models that mimic the endosteal microenvironment enables researchers to discover the causes and improve treatments for blood and immune-related diseases. The aim of this study was to establish a physiologically relevant in vitro model using 3D printed scaffolds to assess the contribution of human cells to the formation of a construct that mimics human endosteum. Melt electrospun written scaffolds were used to compare the suitability of primary human osteoblasts (hOBs) and placenta-derived mesenchymal stem cells (plMSCs) in (non-)osteogenic conditions and with different surface treatments. Using osteogenic conditions, hOBs secreted a dense ECM with enhanced deposition of endosteal proteins, such as fibronectin and vitronectin, and osteogenic markers, such as osteopontin and alkaline phosphatase, compared to plMSCs. The expression patterns of these proteins were reproducibly identified in hOBs derived from three individual donors. Calcium phosphate-coated scaffolds induced the expression of osteocalcin by hOBs when maintained in osteogenic conditions. The tissue-engineered endosteal microenvironment supported the growth and migration of primary human haematopoietic stem cells (HSCs) when compared to HSCs maintained using tissue culture plastic. This 3D testing platform represents an endosteal bone-like tissue and warrants future investigation for the maintenance and expansion of human HSCs. Statement of Significance: This work is motivated by the recent interest in melt electrospinning writing, a 3D printing technique used to produce porous scaffolds for biomedical applications in regenerative medicine. Our team has been among the pioneers in building a new class of melt electrospinning devices for scaffold-based tissue engineering. These scaffolds allow structural support for various cell types to invade and deposit their own ECM, mimicking a characteristic 3D microenvironment for experimental studies. We used melt electrospun written polycaprolactone scaffolds to develop an endosteal bone-like tissue that promotes the growth of HSCs. We combine tissue engineering concepts with cell biology and stem cell research to design a physiologically relevant niche that is of prime interest to the scientific community.